PENERAPAN MODEL TGT BERBANTUAN EDUCAPLAY UNTUK MENINGKATKAN KETERAMPILAN KOLABORASI DAN HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN MATEMATIKA - Pratiwi, Balkis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of collaboration skills and mathematics learning outcomes among fourth-grade students represents a problem requiring an instructional innovation capable of fostering student engagement and cooperation. This study aims to: (1) describe the implementation of the Teams Games Tournament (TGT) learning model assisted by Educaplay in fourth-grade mathematics lessons; (2) improve students' collaboration skills through the implementation of this model; and (3) enhance student learning outcomes following the implementation of the Educaplay-assisted TGT model. This study is a Classroom Action Research (CAR) project conducted over two cycles, with each cycle comprising the stages of planning, action implementation, observation, and reflection. The research subjects were 16 fourth-grade students at SD Muhammadiyah I Purworejo. Data collection techniques included observation, interviews, tests, and documentation, which were analyzed using both quantitative and qualitative descriptive methods. The results indicate that the implementation of the Educaplay-assisted TGT model was carried out successfully in accordance with the model's instructional syntax. Students' collaboration skills improved from 51% in the pre-cycle stage to 61% in Cycle I and 84% in Cycle II. The percentage of learning mastery also increased from 31% in the pre-cycle stage to 81% in Cycle I and 94% in Cycle II. Thus, the Educaplay-assisted Teams Games Tournament (TGT) learning model is effective in improving the collaboration skills and mathematics learning outcomes of fourth-grade students, particularly regarding the topics of area and volume unit measurements.